2019
DOI: 10.1021/jacs.9b04293
|View full text |Cite
|
Sign up to set email alerts
|

Scandium-Promoted Direct Conversion of Dinitrogen into Hydrazine Derivatives via N–C Bond Formation

Abstract: Direct conversion of dinitrogen (N 2 ) into organic compounds, not through ammonia (NH 3 ), is of great significance both fundamentally and practically.Here we report a highly efficient scandium-mediated synthetic cycle affording hydrazine derivatives (RMeN− NMeR′) directly from N 2 and carbon-based electrophiles. The cycle includes three main steps: (i) reduction of a halogen-bridged discandium complex under N 2 leading to a (N 2 ) 3− -bridged discandium complex via a (N 2 ) 2− intermediate; (ii) treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
96
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 61 publications
1
96
0
2
Order By: Relevance
“…CO is isoelectronic with N 2 and serves as a better ligand than N 2 for donor–acceptor bonding with metal centers. It has been shown that dinitrogen coordination and cleavage can be effectively induced by CO with concomitant N−C bond formation mediated by transition metal complexes [18–20] . CO‐induced dinitrogen fixation and activation can serve as an alternative route for dinitrogen transformations [18–21] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CO is isoelectronic with N 2 and serves as a better ligand than N 2 for donor–acceptor bonding with metal centers. It has been shown that dinitrogen coordination and cleavage can be effectively induced by CO with concomitant N−C bond formation mediated by transition metal complexes [18–20] . CO‐induced dinitrogen fixation and activation can serve as an alternative route for dinitrogen transformations [18–21] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that dinitrogen coordination and cleavage can be effectively induced by CO with concomitant N−C bond formation mediated by transition metal complexes [18–20] . CO‐induced dinitrogen fixation and activation can serve as an alternative route for dinitrogen transformations [18–21] . It has been found that many main group atoms can readily react with carbon monoxide in forming various carbonyl complexes [22–30] .…”
Section: Introductionmentioning
confidence: 99%
“…No reaction was observed between 12 and an excess amount of PhSiH 3 .H owever,w hen 12 was treated with 2equiv of MeOTf in benzene at room temperature,adisilylene-linked diamido dititanium bis(triflate) complex {[( acri PNP)TiOTf] 2 [m 2 -N(SiHPh) 2 N]} (13)w as isolated in 40 %yield with release of 2equiv of CH 4 (Scheme 8). [40] This reaction could probably proceed through the dehydrogenative triflation of 12 with one equivalent of MeOTf to give atitanium triflate species like G together with release of CH 4 , followed by s-bond metathesis between aS i ÀHb ond of the PhSiH 2 Nu nit and the bridging Ti À Nb ond in G to yield ac yclodisilylenediazane unit with at itanium hydride species (H). Thed ehydrogenative triflation of H with another molecule of MeOTf would afford 13.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Nowadays, introducing cleaner, safer, and easier accessible nitrogen donors to N-containing organic compounds is an extensively studied topic. 11 In 2009, the Chen group reported a simple, one-step assembly of Ugi adducts suitable for elaboration into a variety of 5-aminoazole compounds through postcondensation modifications by employing concentrated aqueous ammonia as a convenient source ( Figure 1 B). 10 Hutton et al synthesized ustiloxin D utilizing an ammonia–Ugi reaction ( Figure 1 C).…”
Section: Introductionmentioning
confidence: 99%